Envolvimento do receptor de potencial transitório anquirina 1 na analgesia induzida pela fração acetato de etila de Tabernaemontana catharinensis em camundongos - Brum, Evelyne da Silva (2018)
Pain is one condition that limits productivity and reduces the life quality of affected patients. Although exist an arsenal of effective analgesics, there is a great concern related to their safety and adverse effects making their clinical use problematic and motivating many people to choose treatments based on alternative medicine. Tabernaemontana catharinensis is a tree popularly known as cobrina. The diversity of biological actions found in the leaves of T. catharinensis ethyl acetate fraction (Eta) were attributed to the presence of majority compounds, among them the polyphenol gallic acid, known by its antagonist action of transient receptor potential ankyrin 1 (TRPA1). Until the moment, there are preclinical studies supporting the peripheral antinociceptive activity of this fraction. However, it is necessary to elucidate its action mechanism, and a likely Eta target could be the TRPA1 ion channel. The TRPA1 is essential for the detection and transmission of painful stimuli. This channel is activated by naturally occurring irritants and by endogenous oxidizing substances. Moreover, its activation is related to the development and maintenance of several painful conditions. In this context, we verified the involvement of the TRPA1 on Eta’s antinociceptive and anti-inflammatory effect in male Swiss mice (30-35 g). In order to elucidate the Eta’s action mechanism were performed calcium (Ca2+) influx and [3H]-resiniferatoxin specific binding assays. The effects of Eta’s oral treatment (0.01-100 mg/kg) or vehicle (10 ml/kg) were also evaluated by nociceptive (spontaneous nociception, mechanical and cold allodynia) and inflammatory parameters (edema measurement) following intraplantar administration of TRPA1 agonists hydrogen peroxide (H2O2), cinnamaldehyde or allyl isothiocyanate in mice. In addition, the effects of Eta were evaluated on complete Freund's adjuvant (CFA)-induced chronic inflammatory pain model, on postoperative pain model and on acute and chronic peripheral neuropathy induced by paclitaxel. Mice subjected to the CFA-induced chronic inflammatory pain model were used to analyze the fraction’s effect on oxidative parameters, such as tissue oxidation capacity and H2O2 levels. Eta inhibited the TRPA1 agonist-induced Ca2+ influx [Imax = 72.4±1.5%; IC50 = 0.023(0.004–0.135)μg/ml], but not vanilloid 1 (TRPV1) agonist-induced, such as Eta did not displace the [3H]-resiniferatoxin binding. Eta (0.1-100 mg/kg) inhibited the spontaneous nociception (ID50 = 0.043(0.002-0.723)mg/kg), mechanical (ID50 = 7.417(1.426-38.570)mg/kg) and cold allodynia, as well as edema development caused by TRPA1 agonists injections. Moreover, Eta (100 mg/kg) prevented and reversed the CFA-induced chronic inflammatory pain (Imax = 55.8±13.7%, Imax = 80.4±5.1%, respectively) and postoperative pain (Imax = 88.0±11.6%, Imax = 51.3±14.9%, respectively), been also effective in reversing the acute (Imax = 94.4±12.4%) and chronic (Imax = 86.8±8.6%) peripheral neuropathy induced by paclitaxel. These effects seem to occur by TRPA1 channels pathway, and independently of TRPV1 or oxidative mechanisms. Our results demonstrate that Eta-induced antinociception and anti-inflammatory effect occur by TRPA1 inhibition, enabling the use of this preparation as a potential therapeutic agent to treat pathological pains.